Adaptation and Evaluation of a German Sign Language Test - Haug, Tobias (Hamburg Hamburg University Press, 2011)
Despite the current need for reliable and valid test instruments to monitor the sign language acquisition of Deaf children in different countries, very few tests offering strong evidence for their psychometric properties are commercially available. A German Sign Language (DGS) test that focuses on linguistic structures acquired in preschool- and school-aged children (4-8 years old) is urgently needed. The present study uses as a template a test which has sound psychometric properties and has been standardized on another sign language as a starting point for tests of sign languages that are less documented, such as DGS.This book makes a novel contribution to the field by examining linguistic, cultural, methodological, and theoretical issues in the process of the adaptation from the source language test to the target language test, and by providing a model for future test adaptations. It also includes concrete steps for the test development and adaptation process.Adaptation and Evaluation of a German Sign Language Test addresses students and researchers alike who are involved in sign language test development and adaptation. It also provides a comprehensive summary in German.
German
Keywords: Language; Deaf adults; deaf children; Deafness; German Sign Language; DGS; German Sign Language; Test; Language acquisition